International Journal of Web Information Systems (Emerald)
This journal provides a descriptive, analytical, and comprehensive assessment of factors, trends, and issues in the ever-changing field of Web Information Systems. This authoritative research-based publication also offers in-depth explanations of mobile solutions and their specific applications areas, as well as an overview of the future outlook for Web information systems.